Genotype X Environment Interaction of Inbred Lines of Maize (Zea Mays L.) and Stability of Crosses in Kiambu and Embu Counties, Kenya. - Muriuki, J. M.; Njoka, Fredrick M.; Leley, P. K.; Manene, D. W. (My University, 2016)
Despite the fact that virtually all households in Kenya grow maize over 60% of them are net maize buyers because they do not produce enough for their consumption. Kenya’s current food supply situation and outlook give cause for serious concern. Maize is the main staple food averaging over 80% of total cereals (rice, wheat, millet and sorghum) in Kenya. Maize stocks are estimated to be depleted at all levels throughout the country. Due to increasing temperatures as a result of global warming and consequent dropping of water table, there has been shortage leading to increased demand for maize and its products. This study was conducted to determine the stability of respective single crosses in different environments. The trials were conducted in 2012 at experimental stations of Kenya Agricultural and Livestock Research Organization (KALRO), Muguga South and KALRO Embu in Kiambu and Embu counties of Kenya respectively. The study was conducted with 36 crosses. The stability of crosses was determined and interaction between the genotypes and environment was also determined among the crosses.The experiment was laid out in a 6 x 6 lattice complete randomized block design (RBCD) with two replications. Data was subjected to analysis of variance (ANOVA) using Genstat 12 program for individual single crosses as well as for combined environments considering environments as random effects and crosses as fixed effects. Mean separation was done using Tukey’s comparison method at 0.05% significance level. Data on grain yield showed no significant difference between the sites but there was significant difference on grain yield. Data on disease scores where natural infestation was visually scored showed majority of the crosses had a score of one confirming their near immunity status. Further research on stability of the crosses can be done not only in the research sites but also in other regions of Kenya. For grain yield improvement crosses MUL508 x MUL688(entry 9), POPA x MUL141(entry 19), MUL513 x MUL114 (entry 31) and MUL513 x CN244 (entry 33) can further be evaluated and eventually released to farmers as they indicated promising relationship with yield potential compared to other crosses. The results will be useful to breeders and farmers in selecting the potential parental materials for improvement in maize breeding programs.
Keywords: genotype x environment; KALRO; genotypes; mean performance; significant